2018
DOI: 10.1111/apm.12855
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TLR2,TLR4, and TOLLIP polymorphisms for their role in tuberculosis susceptibility

Abstract: Previous studies indicated that single-nucleotide polymorphisms (SNPs) of genes coding for toll-like receptors (TLRs) and toll-interacting protein (TOLLIP) may be involved in the pathogenesis of pulmonary tuberculosis (PTB). This study was designed to investigate potential associations between the polymorphisms in TLR2, TLR4, and TOLLIP and susceptibility to latent tuberculosis infection (LTBI) or subsequent PTB in a Chinese Han population. A total of 209 PTB and 201 LTBI patients and 204 healthy control subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
0
12
1
1
Order By: Relevance
“…The discrepancies between the aforementioned results may be attributed to the different sample sizes and ethnicities [37]. Our results were also differing from our previous study [38], which demonstrated that polymorphisms in TOLLIP affected the risk of pulmonary TB. The different results may be due to the different study designs.…”
Section: Discussioncontrasting
confidence: 99%
“…The discrepancies between the aforementioned results may be attributed to the different sample sizes and ethnicities [37]. Our results were also differing from our previous study [38], which demonstrated that polymorphisms in TOLLIP affected the risk of pulmonary TB. The different results may be due to the different study designs.…”
Section: Discussioncontrasting
confidence: 99%
“…The power of our study design was assessed by using the Power and Sample Size Calculation software 73 . We calculated the power for each SNPs under an allelic model as described previously 74 . The frequency of each SNP in the two cohorts was sufficient to provide reasonable power (>80%) to detect an allele/genotype effect with OR 2.0 or above (Table 7).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 209 PTB and 356 close contacts of individuals with sputum-positive PTB were enrolled between 2013 and 2014. The selection of sample size was based on previous studies [2123]. All of the participants were recruited from the West China Hospital of Sichuan University (Sichuan, China), and they are all genetically unrelated Chinese Han people.…”
Section: Methodsmentioning
confidence: 99%